Scenario-Based Analysis of Hydraulic Response in the Senapelan River Reach - Daly Riandi; Rizki Ramadhan Husaini (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2026)
The absence of long-term observed hydrological data poses a significant challenge for urban flood management. This study addresses data scarcity in the Kedungsari reach of the Senapelan River, Pekanbaru, Indonesia, by combining 1D steady-flow hydraulic modeling with empirical hydrological estimation to determine the channel's critical bankfull capacity and its corresponding return period. The model isolated the maximum safe bankfull capacity at 17.20 m³/s, identifying Cross-Section 4 as the primary hydraulic bottleneck. Mapping this physical capacity onto the regional design flood frequency curve revealed that the existing channel corresponds to a low return period of approximately 1.5 years. Consequently, the channel is severely undersized, failing to contain a standard 2-year frequent flood (24.70 m³/s) or the legally mandated 10-year extreme event (33.26 m³/s).